UPAYA GURU AKIDAH AKHLAK DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI MTS HIDAYATUL MUBTADI’IN TASIKMADU MALANG - Khalimatus Sa’diyah; Anwar Sa’dullah; Nur Hasan (VICRATINA, 2022)
Self-motivation to continue learning is very important for every student, Based on the results of the research that has been done, the researchers can draw the following conclusions: (1) Student learning motivation at MTs Hidayatul Mubtadi'in Tasikmadu Malang. Students who have a high interest in taking lessons seriously, actively, and diligently do the tasks given by the teacher. (2) The efforts of Akidah Akhlak teachers in improving student learning motivation at MTs Hidayatul Mubtadi'in Tasikmadu Malang. The efforts of Akidah Akhlak teachers in increasing student learning motivation are as follows: first, clarifying the goals to be achieved. Second, provide learning resources. Third, give advice. Fourth, give proper praise. Fifth, create a pleasant atmosphere in learning. Sixth, provide tests and assessments. (3) The inhibiting and supporting factors faced by Akidah Akhlak teachers in increasing students' learning motivation at MTs Hidayatul Mubtadi'in Tasikmadu Malang. a. The inhibiting factors are as follows: lack of understanding of students on the material being taught, and inadequate facilities. b. Supporting factors are as follows: students have a strong enough motivation, and adequate school facilities.